UMKM DIMASA PANDEMI COVID 19 BERDAMPAK PADA TEKNOLOGY DAN DIGITALISASI PADA PUSAT OLEH OLEH RAHMA DI DESA KENDALREJO - Hisnul Hisnul; Pompong Budi Setiadi; Sri Rahayu (Sekolah Tinggi Ilmu Ekonomi Dr Kh Ez Mutaqien, 2022)
The impact of the industrial revolution 4.0 and the Covid-19 pandemic that occurred had an impact on the implementation of the digital economy, it also provided opportunities and challenges for the economic sector. In this study, we will review the application of the implementation of the digital economy to MSMEs, which can be an alternative solution to deal with these conditions. UMKM technology and digital business are defined as a type of venture involving the latest technology in its practices and development. The application of digital concepts in business development can create new business models, experiences and operational codes that will later help to influence consumerism in both products and services that are offered. From competition, networking and networking and are networked with umkm products advanced through classes and go international. This research is focused on UMKM in the culinary sector, namely a case study at the Rahma gift center in Kendalrejo Village which had previously been operating before the Covid-19 outbreak hit Indonesia.